2021
DOI: 10.1038/s41598-021-84635-6
|View full text |Cite
|
Sign up to set email alerts
|

Ketone body 3-hydroxybutyrate as a biomarker of aggression

Abstract: Human aggression is a complex behaviour, the biological underpinnings of which remain poorly known. To gain insights into aggression biology, we studied relationships with aggression of 11 low-molecular-weight metabolites (amino acids, ketone bodies), processed using 1H nuclear magnetic resonance spectroscopy. We used a discovery sample of young adults and an independent adult replication sample. We studied 725 young adults from a population-based Finnish twin cohort born 1983–1987, with aggression levels rate… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 65 publications
0
6
0
Order By: Relevance
“…Increased hepatic even/odd chain fatty acid ratio and reduced leptin levels in RYGB support the hypothesis that RYGB leads to upregulated lipolysis as reflected by increased levels of the ketone body 3-hydroxybutyrate in RYGB animal plasma. 3-Hydroxybutyrate is produced by the liver in lipolysis and serves as the primary energy substrate via beta-oxidation and acetyl-CoA for the TCA cycle when glucose is depleted [70]. During lipolysis, long-chain fatty acids can be transported only within chylomicrons, which are therefore highly upregulated [71].…”
Section: Rygb Surgery Results In Elevated Lbp Not As a Results Of Inf...mentioning
confidence: 99%
“…Increased hepatic even/odd chain fatty acid ratio and reduced leptin levels in RYGB support the hypothesis that RYGB leads to upregulated lipolysis as reflected by increased levels of the ketone body 3-hydroxybutyrate in RYGB animal plasma. 3-Hydroxybutyrate is produced by the liver in lipolysis and serves as the primary energy substrate via beta-oxidation and acetyl-CoA for the TCA cycle when glucose is depleted [70]. During lipolysis, long-chain fatty acids can be transported only within chylomicrons, which are therefore highly upregulated [71].…”
Section: Rygb Surgery Results In Elevated Lbp Not As a Results Of Inf...mentioning
confidence: 99%
“…This evidence of overlap in genetic liability to individual variation in SOC with psychological well-being, dimensions of mental health and personality creates opportunities for further research. The search for endophenotypes that mediate effects of dispositional genes on observed phenotypes of psychopathology [ 44 ] can be extended to endophenotypic pathways for risk-relevant behavioral precursors as illustrated by a study suggesting a novel metabolic biomarker, ketone body 3-hydroxybutyrate, of aggression [ 45 ]. Such research is responsive to the call to create a holistic framework for enhanced understanding of mental health traits, proposed by the National Institute of Mental Health’s Research Domain Criteria (RDoC) Initiative [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Using high-throughput 1 H nuclear magnetic resonance spectroscopy (NMR) to profile the metabolites, the study identified a significant negative association of plasma valine and leucine with depression. The same group previously identified ketone body 3-hydroxybutyrate as a biomarker of aggression (Whipp et al, 2021 ), highlighting the potential of metabolomic biomarkers in different types of mental health problems.…”
mentioning
confidence: 92%